Validation of Nd2NiO4+δ as Oxygen Electrode Material for Intermediate Temperature Solid Oxide Cells with LSGM Electrolyte - Montenegro Hernandez, Alejandra (2013)
The oxygen reduction reaction (ORR) was studied by Electrochemical Impedance Spectroscopy (EIS) for Nd2NiO4+δ (NNO) electrodes deposited on La0.9Sr0.1Ga0.8Mg0.2O2.85 (LSGM) electrolyte. The influence of NNO microstructure on the electrochemical performance was evaluated. The EIS measurements were carried out as a function of temperature (500<T<750ºC) and oxygen partial pressure (10-4<pO2<1atm). Three contributions associated with the ORR were identified: at high (HF), medium (MF) and low frequencies (LF). The HF contribution was associated with oxygen ion transfer trough electrode/electrolyte interphase. The MF contribution was attributed to oxygen ions diffusion within the NNO. The LF contribution was related to O2-dissociative adsorption for NNO obtained by chemical routes, where the particle sizes are smaller. If NNO were obtained by Solid State Reaction, the LF element was associated with a convolution of dissociative adsorption and gas diffusion processes.